Introduction - Abd Rahman, Shukran; Shuib, Munir (IIUM Press, 2009)
As life is becoming more complex and society turns to be more multifaceted, the need to prepare individuals with necessary quality is essential so as to make them function judiciously and experience life harmoniously. The never ending issue on human development encompasses the role of HE in producing human resources who serve as important agents in nation building. Around the globe, Higher Learning Institutions (HLls) have been playing the role of producing manpower or workforce for industries, and other job sectors. In line with changes in social, technological and human lifestyles, the role of HLls has changed. Governments of virtually all countries, including Malaysia, have embarked on Higher Education (HE) reforms meant to strategise the effort of strengthening their HLls so that they are relevant to the current need, and prepare workforce to face the future. In this regard, this chapter introduces HE reforms in some selected countries, which could drive some awareness on the importance of HE in workforce development later discussed in the rest of this book.